2019
DOI: 10.1093/asj/sjy335
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Effects of Breast Implant Particulate Shedding: Comparison With Orthopedic Implants

Abstract: Currently, there is a dearth of information regarding the degree of particle shedding from breast implants (BIs) and what are the general biological consequences of BI debris. Thus, it is unclear to what degree BI debris compromises the long-term biological performance of BIs. For orthopedic implants, it is well established that the severity of biological reactivity to implant debris governs long-term clinical performance. Orthopedic implant particulate debris is generally in the range of 0.01 to 100 μm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 111 publications
2
35
0
1
Order By: Relevance
“…Similar to BIA-ALCL, case reports of CD30-positive ALK-negative ALCL in patients with dental [ 50 ], gastric lap band [ 51 ], gluteal [ 52 ], and silicone-containing port device implants [ 53 ] have subsequently emerged [ 48 ]. While theories of lymphomagenesis by a proposed mechanism of mechanical friction have been suggested [ 54 ], evidence remains limited in light of the fact that the capsular-implant interface is typically “slick”.…”
Section: Etiology Of Bia-alclmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to BIA-ALCL, case reports of CD30-positive ALK-negative ALCL in patients with dental [ 50 ], gastric lap band [ 51 ], gluteal [ 52 ], and silicone-containing port device implants [ 53 ] have subsequently emerged [ 48 ]. While theories of lymphomagenesis by a proposed mechanism of mechanical friction have been suggested [ 54 ], evidence remains limited in light of the fact that the capsular-implant interface is typically “slick”.…”
Section: Etiology Of Bia-alclmentioning
confidence: 99%
“…A study of particles present around failed silicone orthopedic implants identified billions of particles less than 1 μm in size [ 57 ]. Failure of metal and polyethylene implants is linked to an innate immune system response in which activated macrophages become overwhelmed with particulate wear debris and subsequently release inflammatory factors that indirectly promote a T-cell response by lymphocyte chemotaxis and replication [ 54 , 58 ]. Such a mechanism—involving the capture of silicone-containing particles by macrophages followed by macrophage activation, cytokine production, and apoptosis—has been proposed for silicone-induced granuloma of the breast implant capsule [ 59 ].…”
Section: Etiology Of Bia-alclmentioning
confidence: 99%
“…Authors have postulated that all implants produce a variable degree of implant debris over time. 44 In fact, friction between the implant surface and the overlying tissues can cause chronic inflammation. Friction and wear can lead to the breaking off of tiny silicone particles from the implant surface, which can also aggravate inflammation through macrophage digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors have been implicated 14 (14), including the use of textured surface implants, a local inflammatory reaction, 15 and impaired host immunity by mutations in the JAK3-STAT pathway and MYC/TP53 deregulation. 16 18 The average time from implant to lymphoma development is approximately 9 years. 19 The most frequent clinical manifestation is the presence of limited effusion (seroma), which occurs in almost 70% of cases.…”
Section: Introductionmentioning
confidence: 99%